The Kontribusi diferensiasi diri dan karakteristik kepribadian neurotisisme terhadap kepuasan hubungan mahasiswa perempuan di Jabodetabek - Siregar, Shinta; Aditya, Yonathan (Jurnal Psikologi Ulayat, 2024)
Dating is a common experience among students entering young adulthood, a stage often marked by the challenge of forming intimate connections. Relationship quality plays a key role in determining dating’s impact on students. Therefore, it is essential for dating students to assess their relationship quality and understand the influencing factors. Relationship quality can be evaluated by measuring relationship satisfaction. This study investigated the contributions of differentiation of self and neuroticism toward relationship satisfaction of female students in Jabodetabek. The data was collected from 84 participants via electronic questionnaires distributed through social media and directly to universities in Jabodetabek. The findings indicated that both differentiation of self and neuroticism significantly contributed to relationship satisfaction. Differentiation of self not only enhances relationship satisfaction but can also mitigate the negative impact of neuroticism.